ANALISIS PENGELOLAAN KEUANGAN DESA PADA PEMERINTAH DESA PASAR LAMA KECAMATAN KARANG INTAN KABUPATEN BANJAR - yudi rahman lisda ramadhani (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Accounting Department of the Banjarmasin Pancasetia Economics School in 2015. The study was entitled "Analysis of Village Financial Management in the Pasar Lama Village Government in KarangIntan District, Banjar Regenc. This study aims to describe the Analysis of Village Financial Management in the Pasar Lama Village Government in KarangIntan District, Banjar Regency, covering planning, implementation, administration, reporting and accountability of village finance. Know and analyze how the comparison of Village Financial Management according to the format of Banjar Regent Regulation Number 3 of 2017 with Village Financial Management in the Pasar Lama Village Government. This study uses a qualitative research method with a descriptive analysis approach. File collection techniques are carried out by interview, observation, documentation and literature. File analysis uses interactive analysis techniques, namely through collectionfile, reduction file, presentation file and conclusion drawing. The results showed that although there were errors in the administration of the arrangement but overall the financial management of Pasar Lama Village was almost the same as the management according to the format of the Banjar Regent Regulation Number 3 of 2017. Keywords: Analysis, Village Finance, DesaPasar Lama.